The Passions and the Interests. Political Arguments for Capitalism before Its Triumph - Hirschman, Albert O. (Princeton Princeton University Press, 1977)
Hirschman ... explores in this lucid and elegant essay the sets of ideas about the likely effects on the social order of commercial expansion and the rising spirit of capitalism advanced by political philosophers, moralists, and literary commentators of the seventeenth and eighteenth centuries. This unpretentious little book is an intellectual treat and a superb contribution in particular.
Keywords: History